Anthropogenic impacts on Tiger frog Hoplobatrachus tigerinus, at Biratnagar and its surroundings, Nepal - Sah, Minu Kumari; Subba, Bharat Raj (Nepalese Journal of Biosciences, 2013)
DOI: http://dx.doi.org/10.3126/njbs.v2i0.7505 Nepalese Journal of Biosciences 2 : 156-157 (2012)